2016
DOI: 10.1080/19336918.2016.1225631
|View full text |Cite
|
Sign up to set email alerts
|

aPKCζ affects directed cell migration through the regulation of myosin light chain phosphorylation

Abstract: Cell motility is an essential cellular process for a variety of biological events. It requires cross-talk between the signaling and the cytoskeletal systems. Despite the recognized importance of aPKCz for cell motility, there is little understanding of the mechanism by which aPKCz mediates extracellular signals to the cytoskeleton. In the present study, we report that aPKCz is required for the cellular organization of acto-non-muscle myosin II (NMII) cytoskeleton, for proper cell adhesion and directed cell mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…We next investigated the localization of other apical proteins, including the actomyosin components, mono- and di-phosphorylated Myosin Light Chain (pMLC and ppMLC), Rock1, a Rho-associated kinase that phosphorylates and activates myosin light chain, and F-actin. We analyzed the localization of the Crumbs complex proteins PatJ, and aPKC, a regulator of non-muscle Myosin2 contexts (Biehler et al, 2021; Petrov et al, 2017; Roper, 2012; Sidor et al, 2020). Membrane segmentation allowed us to systematically quantify several parameters, including apical surface area, cell elongation, and the intensity of junctional protein accumulation (Figure 4A, Figure 4-figure supplement 1C).…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the localization of other apical proteins, including the actomyosin components, mono- and di-phosphorylated Myosin Light Chain (pMLC and ppMLC), Rock1, a Rho-associated kinase that phosphorylates and activates myosin light chain, and F-actin. We analyzed the localization of the Crumbs complex proteins PatJ, and aPKC, a regulator of non-muscle Myosin2 contexts (Biehler et al, 2021; Petrov et al, 2017; Roper, 2012; Sidor et al, 2020). Membrane segmentation allowed us to systematically quantify several parameters, including apical surface area, cell elongation, and the intensity of junctional protein accumulation (Figure 4A, Figure 4-figure supplement 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, myosin-11 (MYH11, smooth muscle-specific myosin heavy chain) [ 33 ] was also at the tip of the leading cell edge, which was colocalized with MLC 20 ( Figure 1 B). Because myosin activation by MLC 20 phosphorylation is associated with migration [ 3 , 4 ], we also assessed the spatial localization of phosphorylated MLC 20 , which was found at the leading edge ( Figure 1 C). These results suggest that a fraction of smooth muscle myosin localizes at the leading cell edge during migration.…”
Section: Resultsmentioning
confidence: 99%
“…Smooth muscle myosin II has been traditionally thought to localize in the cytoplasm solely [ 1 ] and modulates cell migration by affecting stress fiber formation, focal adhesion assembly, and the retraction of the rear [ 3 , 4 ]. In this study, MLC 20 and MYH11 were found at the edge of lamellipodia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations